Increase in the capacity of a CDMA Hierarchical Cellular System by assigning cells based on user mobility - Morales V., Aurelio (2002)
Microcells are a conceptual solution in areas with high traffic load. A hierarchical CDMA cellular system (microcells overlaid with umbrella macrocells), which shares the same frequency channel across the system (reuse pattern of one) and applies soft handoff between the cells, shown to have full connectivity between the microcells and the overlaying macrocells without capacity degradation. To keep the handoff rate in a two-tier cellular system at an acceptable level, users mobility shouldbe utilized in cell assignment. In this paper, we study the increment of capacity of a hierarchical CDMA cellular system based on users mobility. As it is described in [3], low mobility users (with speed v<Vo = velocity threshold) should undergo handoffs at microcell boundaries, while high mobility users (with speed v>Vo) should undergo handoffs at macrocell boundaries. Therefore, considering the previous study and the design characteristics of a CDMA Network, a niodel is implemented, and after its simulation with MATLAB, the respective results and conclusions are presented.